The CFD Analysis of Ventilation and Smoke Control System with Jet Fan in A Parking Garage - (:unkn) unknown (My University, 2020)
Basements of buildings are generally used as parking garages and vehicles located in there release harmful gases. It is generally not possi-ble to ventilate parking garages with natural ventilation methods. For this reason, ventilation systems should be used to keep the concen-tration of harmful gases below certain limits. One of these ventilation systems is jet fan system. It can also be used for smoke control and exhaust of harmful gases in case of fire. In this study, the jet fan system was designed for a parking garage and its performance has been observed by Computational Fluid Dynamics (CFD). Carbon monoxide concentration and air velocity parameters were investigated accord-ing to the different car occupancy rates with the CFD analyses for daily ventilation. In the results, when the number of cars increased, the air velocities decreased in the areas where the cars located and exhaust of the CO gas took longer time. In fire analyses, the same parame-ters were analyzed according to the different jet fan hanging heights. In the fire ventilation results, when the jet fan hanging height was in-creased, distribution of the air velocity profiles changed and it took longer time to exhaust the CO gas from the car park.